2016
DOI: 10.1038/aps.2016.123
|View full text |Cite
|
Sign up to set email alerts
|

Polydatin ameliorates Staphylococcus aureus-induced mastitis in mice via inhibiting TLR2-mediated activation of the p38 MAPK/NF-κB pathway

Abstract: Recent studies show that Polydatin (PD) extracted from the roots of Polygonum cuspidatum Sieb, a widely used traditional Chinese remedies, possesses anti-inflammatory activity in several experimental models. In this study, we investigated the anti-inflammatory effects of PD on Staphylococcus aureus-induced mastitis in mice and elucidated the potential mechanisms. In mice with S aureusinduced mastitis, administration of PD (15, 30, 45 mg/kg, ip) or dexamethasone (Dex, 5 mg/kg, ip) significantly suppressed the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 35 publications
(34 reference statements)
5
42
0
Order By: Relevance
“…Previous studies showed that AP-1 and NF- κ B could be activated by the phosphorylation of ERK, JNK, and P38 [ 23 ]. Activation of AP-1 and NF- κ B could promote the production of proinflammatory factors and profibrotic factors in pulmonary fibrosis [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that AP-1 and NF- κ B could be activated by the phosphorylation of ERK, JNK, and P38 [ 23 ]. Activation of AP-1 and NF- κ B could promote the production of proinflammatory factors and profibrotic factors in pulmonary fibrosis [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The excessive production of pro‐inflammatory cytokines increases the immune response, which in turn results in inflammatory cascade and tissue injury .Thus, inhibiting the release of inflammatory cytokines may be a target for anti‐inflammatory drug therapies. Therefore, in this study, we used macrophages instead of primary endometrial epithelial cells to explore the underlying mechanism of PD, which could have more general applicability—that is, PD may also play a similar role in other inflammatory diseases that have been confirmed in our previous studies . In this research, we evaluated the protective effects of PD in vivo using histological analyses, including H&E, immunofluorescence staining of phosphorylated NF‐κB involved in the regulation of the inflammatory process and the TUNEL assay as well as some of the crucial apoptosis‐related proteins.…”
Section: Discussionmentioning
confidence: 99%
“…qPCR and Western blot were carried out according to the manufacturer's instructions as previously reported . qPCR was performed using SYBR Premix DimerEraser (Takara) on a 7900HT system.…”
Section: Methodsmentioning
confidence: 99%
“…qPCR and Western blot were carried out according to the manufacturer's instructions as previously reported. 31 qPCR was performed using SYBR Premix DimerEraser (Takara) on a 7900HT system. The relative expression of miR-148a and specific mRNAs was normalized against internal controls (U6 or GAPDH) using the 2 −ΔΔCt method.…”
Section: Qpcr and Western Blotmentioning
confidence: 99%